2021
DOI: 10.1111/jch.14256
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinic and ambulatory blood pressure with new‐onset atrial fibrillation: A meta‐analysis of observational studies

Abstract: Various studies have shown that hypertension, 1,2 through different mechanisms, 3 is an important risk factor for incident atrial fibrillation (AF) which in turn increases cardiovascular risk. 4 Clinic blood pressure (BP) recording is traditionally used for diagnosis and management of hypertension. However, it has been largely reported that ambulatory BP is superior to clinic BP in predicting cardiovascular outcome. [5][6][7][8][9][10][11] In such a context, some studies have also evaluated whether ambulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A recent meta-analysis showed that daytime, nighttime, and 24-h systolic blood pressure (BP) are similarly associated with future AF and that ambulatory systolic BP is a better predictor than clinic BP [ 69 ]. The mechanism involved in the effect of hypertension on AF is not well known but two main mechanisms are proposed.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis showed that daytime, nighttime, and 24-h systolic blood pressure (BP) are similarly associated with future AF and that ambulatory systolic BP is a better predictor than clinic BP [ 69 ]. The mechanism involved in the effect of hypertension on AF is not well known but two main mechanisms are proposed.…”
Section: Resultsmentioning
confidence: 99%
“…Several prospective cohort studies have shown that a strong risk factor for cardiovascular disease (CVD), including atrial fibrillation, is hypertension (29). Furthermore, in the study reported by Coccina F et al, both ambulatory and clinical systolic blood pressure prospectively predicted the onset of AF and daytime, nighttime, and 24-hour systolic blood pressure had similar correlations with future AF (42). Nevertheless, these studies covered a limited subgroup of population in general and were based on systolic blood pressure, potentially biasing the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a recent meta-analysis suggests that ambulatory (versus clinic) SBP predicts incident AF better and that daytime, night-time and 24-hour SBP are similarly associated with future AF. 45 Whether BP lowering guided by ambulatory BP measurements is stronger than BP lowering guided by clinic BP lowering in reducing new-onset AF requires further study.…”
Section: Early Transition To Management Of Atrial Fibrillation In Hyp...mentioning
confidence: 99%